2011
DOI: 10.5380/rf.v41i2.21876
|View full text |Cite
|
Sign up to set email alerts
|

DESEMPENHO DE CINCO PROCEDÊNCIAS DE Grevillea robusta NO NORTE DO PARANÁ

Abstract: A Grevillea robusta é uma espécie arbórea nativa das regiões subtropicais costeiras da Austrália. Foi uma das primeiras plantas da Austrália cultivada fora de sua área de ocorrência natural, principalmente como ornamental. Essa espécie é recomendada para plantio nas regiões mais quentes do Paraná, sendo apreciada para arborização de lavouras de café. Com o objetivo de comparar o desempenho de procedências de G. robusta, instalou-se um experimento no município de Londrina, PR. Quatro procedências australianas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Data from a provenance tests carried out in northern State of Paraná and elsewhere in Brazil (Sebbenn et al, 1999;Martins et al, 2006;Leal and Ramos, 2011) have demonstrated higher performances of recently introduced provenances in comparison to previously introduced material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a provenance tests carried out in northern State of Paraná and elsewhere in Brazil (Sebbenn et al, 1999;Martins et al, 2006;Leal and Ramos, 2011) have demonstrated higher performances of recently introduced provenances in comparison to previously introduced material.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter new provenances were reintroduced in Brazil and institutions as Instituto Florestal de São Paulo (IF-SP), Embrapa Florestas (CNPF) and Instituto Agronômico do Paraná (IAPAR) which demonstrated it potential Paraná, São Paulo and Mato Grosso do Sul States. Differences between them have been reported (Sebbenn et al, 1999;Martins et al, 2005;Martins et al, 2006;Leal and Ramos, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…The species is endemic to Queensland, i.e., eastern Australia, and is widely distributed in southeast Asia, Africa, and the southern part of North America and South America [8]. In the last three decades, G. robusta was introduced from Australia to all regions of the world, viz., China, Eritrea, Ethiopia, India, Indonesia, Jamaica, Kenya, Laos, Malawi, Malaysia, Mauritius, Nepal, Pakistan, the Philippines, South Africa, Sri Lanka, Tanzania, Uganda, the United States of America, Vietnam, Zambia, and Zimbabwe [9][10][11][12][13][14][15][16]. In India, the species is distributed in approx.…”
Section: Introductionmentioning
confidence: 99%